2015
DOI: 10.1016/j.bbr.2014.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Pain and depression comorbidity: A preclinical perspective

Abstract: Pain and depression are two highly prevalent and deleterious disorders with significant socioeconomic impact to society. Clinical observations have long recognized the co-existence and interactions of pain and depression. However, the underlying mechanisms of pain-depression comorbidity and their dynamic interactions remain largely unknown. Preclinical animal studies may provide critical information for the understanding of this important comorbidity. This review analyzed the current preclinical evidence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 78 publications
(109 reference statements)
4
96
0
1
Order By: Relevance
“…For example, previous clinical investigations have observed frequent comorbidity of pain and depression [47-49]. Not only do these two symptoms coexist, they often respond to the same treatment and exacerbate each other [17]. In addition to pain, urinary dysfunction has also been reported to be correlated with severity of depression [50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous clinical investigations have observed frequent comorbidity of pain and depression [47-49]. Not only do these two symptoms coexist, they often respond to the same treatment and exacerbate each other [17]. In addition to pain, urinary dysfunction has also been reported to be correlated with severity of depression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Pain and depression frequently manifest together. Epidemiological studies have shown that the prevalence of depression in patients with pain is higher compared with that when these two conditions are separately evaluated [1][2][3]. Approximately 30% of patients in pain experience depression [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Depression, in turn, is conducive to intensification of pain (cf. Li, 2015;Wojtyna, 2012), as well as cognitive distortions, consisting of negative perception of self, reality, and the future, thus it may be directly connected with reduction of hope (cf. Williams, 1997;Wójcik & Wojtyna, 2008).…”
Section: Discussionmentioning
confidence: 99%